LITERATURE REVIEW: COMPETITIVE STRATEGY, COMPETITIVE ADVANTAGES, AND MARKETING PERFORMANCE ON E-COMMERCE SHOPEE INDONESIA - Ding Chong; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2022)
Facilitated all economic and business activities globally in the 4.0 Industrial Revolution era. Moreover, buying and selling activities that are usually offered conventionally are now made digitally, which is called E-commerce. E-commerce began to develop in Indonesia in 1999 with a buying and selling platform, namely Kaskus. The public could not entirely accept the emergence of e-commerce due to various factors, such as the quality of the products offered. Until 2009, different e-commerce platforms in Indonesia began to develop, one of which was Shopee. To deal with the existing Competitive Advantages, Shopee uses several Competitive Strategies to analyze the advantages in the Marketing Performance, Cost Leadership, Alliance, and Innovation strategies.